IMPLEMENTASI METODE SUPPORT VECTOR MACHINE (SVM) PADA CITRA FUNDUS RETINA MATA UNTUK DETEKSI PENYAKIT GLAUKOMA - Alifah Akbar Pertiwi; Aryo Nur Utomo (JURNAL REKAYASA INFORMASI, 2023)
Eyes is vital organs that are in humans, for man needs eyes to see and as one of the organs the balance of the body. An eye disease that causes enough harm one of these is glaucoma. Glaucoma is a disease the cause of blindness number two after a cataract. Glaucoma is a disease the cause of blindness number two after a cataract. This has been one of factors that the area really needed always evolves in developing a tool that is capable of detection. Was used in the study of a programming language python that is a programming language that best uses machine learning. Assisted by streamlit framework to develop website, local algorithm binary his patterns as algorithms the extraction of pictures image, and support algorithm vector machine as algorithms classifications the results of the extraction of image, one in which will classifying / grouping of the image test group / health eyes are part of the eye in which have the disease glaucoma. Keywords: Website, Support Vector Machine, Local Binary Pattern, Glaucoma, Machine Learning.